ANTIBACTERIAL ACTIVITY OF ALOE VERA LEAF INFUSE [Aloe barbadensis Miller] - Sulistyani, Nunung; Kurniati, Eni; Yakup, -; Cempaka, Risa Ayu (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2016)
The aim of this studi is to examine the antibacterial activity of aloe vera leaf infuse (Aloe barbadensis Miller) against human pathogens such as Pseudomonas aeroginosa, Salmonella typhi, Staphylococcus aureus, dan Streptococcus pneumonia. Antibacterial activity test of 20, 40, and 60% aloe vera leaf infuse was using agar well diffusion method. The antibacterial activity is indicated by the formation of a clear zone around the wells. All the concentration of aloe vera leaf infuse (Aloe barbadensis Miller) showed signiï¬ cant antibacterial activity against Pseudomonas aeroginosa, Salmonella typhi, Staphylococcus aureus, but did not show antibacterial activity against Streptococcus pneumonia. Aloe vera leaves infuse at a concentration of 60% can inhibit the growth of Pseudomonas aeroginosa indicated by the formation of a clear zone (16.5 mm), the bacteria Salmonella typhi (34 mm), and Staphylococcus aureus (15 mm). The research recommended aloe vera leaf would be suitable for use as antibacterial agent of disease caused by Pseudomonas aeroginosa, Salmonella typhi, and Staphylococcus aureus.Â